2000
DOI: 10.1149/1.1394124
|View full text |Cite
|
Sign up to set email alerts
|

On the Nature of the Luminescence of Sr[sub 2]CeO[sub 4]

Abstract: Recently efficient blue-white luminescence from Sr 2 CeO 4 was reported. 1 The emission was assigned to a ligand-to-metal chargetransfer transition of Ce 4ϩ . Charge transfer (CT) emission from Ce 4ϩ , or any other tetravalent lanthanide, had not been reported previously. Here, further research on the luminescence of Sr 2 CeO 4 is reported. Three topics are discussed. First the nature of the luminescence is investigated. The results provide evidence that the efficient blue-white emission is not related to a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
54
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 10 publications
8
54
0
Order By: Relevance
“…All samples exhibit a high intensity and broad absorption band in the spectral range of 250-450 nm, assigned to the ligand-to-metal charge-transfer states O → Ce 4+ (LMCT) from O 2 2− ligand to Ce 4+ ion. The LMCT absorption bands are asymmetric and correlate with those of van Pieterson et al [22] who calculated the position of O → Ce 4+ LMCT absorption band of Sr 2 CeO 4 compound using an empirical formula of optical electronegativity data given by Jørgensen [23]. However, these two absorption bands observed for the Sr 2 CeO 4 system were related to different Ce 4+ -O 2 2− distances in the lattice.…”
Section: Photoluminescence Behaviorsupporting
confidence: 68%
See 1 more Smart Citation
“…All samples exhibit a high intensity and broad absorption band in the spectral range of 250-450 nm, assigned to the ligand-to-metal charge-transfer states O → Ce 4+ (LMCT) from O 2 2− ligand to Ce 4+ ion. The LMCT absorption bands are asymmetric and correlate with those of van Pieterson et al [22] who calculated the position of O → Ce 4+ LMCT absorption band of Sr 2 CeO 4 compound using an empirical formula of optical electronegativity data given by Jørgensen [23]. However, these two absorption bands observed for the Sr 2 CeO 4 system were related to different Ce 4+ -O 2 2− distances in the lattice.…”
Section: Photoluminescence Behaviorsupporting
confidence: 68%
“…Moreover, the tetravalent cerium ion (Ce 4+ , 4f 0 ) has an empty electronic configuration. The CeO 2 host exhibits a strong UV absorption arising from the ligand-to-metal charge-transfer states O → Ce 4+ (LMCT) from O 2 2− ligand to Ce 4+ ion that can act as a promising luminescent material [22]. Fig.…”
Section: Photoluminescence Behaviormentioning
confidence: 99%
“…Using (O) = 3.2 [15], (Tb) = 0.95 [16], the CTB of Tb 3+ in oxide can be calculated as 148 nm. So, the former is attributed to the CTB of Tb 3+ .…”
Section: Resultsmentioning
confidence: 99%
“…In these materials the optical transitions are based on a ligand-to-metal charge transfer (CT) from O 2-to Ce 4? [122,123]. It was found that the addition of Sn 4?…”
Section: Blue Phosphors-other Hostsmentioning
confidence: 99%